Estudo fitoquímico de Annona squamosa L. e atividades biológicas dos seus constituintes - Formoso, Dianne Dominguez (2023)
PHYTOCHEMICAL STUDY OF ANNONA SQUAMOSA L. AND BIOLOGICAL ACTIVITIES OF ITS CONSTITUENTS. Annona squamosa L. belongs to the Annonaceae family which is a promising natural source of metabolites with potential therapeutic and medicinal functions. In 1982, the first member of a new class of secondary metabolites in plants was reported, which currently comprises a group of 430 natural compounds found almost exclusively in plants of the Annonaceae, called Annonaceae acetogenins (ACGs). The present work aimed to investigate the phytochemical composition of extracts of the species A. squamosa L. through bioguided studies in the search for biologically active substances, from the evaluation of the efficiency of extracts and isolated substances. In the study, three acetogenins were isolated from leaves and seeds of A. squamosa L.1D and 2D NMR analyses were performed, which confirmed the presence of three acetogenins, being isomers. They are isomers of Squamostin, containing a smaller carbon chain between the lactone and the first tetrahydrofuran ring. Isomers are differentiated by the position and stereochemistry of their hydroxyl groups. The results showed a monoisotopic mass of m/z 639.4818 [M+H]+, corresponding to a molecular formula C37H67O8+ and a mass error of 1.02 ppm for the acetogenin isomers. Two lignans were also isolated from the leaves of the plant; Yanganbim is another lignan derived from yangambim, but still unknown in the literature (structure under more detailed study). Subsequently, 6 compounds within the acetogenin class of A. squamosa seed acetate extract were isolated and purified by bench column, by normal phase, which were characterized by the spectroscopic technique of 1D and 2D NMR and High Resolution Mass Spectrometry (UPLC-QTOF-MS/MS). After confirmation of purity by NMR and UPLC-QTOF- MS/MS; Eleven molecules isolated from A. squamosa were tested for their ability to inhibit the growth of the bacterium Xanthomonas citri spp. Citri, which causes Citrus Cancer. The results indicated a bacteriostatic activity, that is, the ability to inhibit the growth of the bacteria, which may be useful in controlling the disease in citrus plantations. The insecticidal activities of A. squamosa extracts against Spodoptera frugiperda and the anticancer activity against human breast adenocarcinoma MCF-7, lung cancer A549 and normal human MRC-5 cells were also evaluated. The extracts showed potential as anticancer phytopharmaceuticals, indicating the possibility of developing new therapeutic candidates from these compounds.